An app-based training for adolescents with problematic digital-media use and their parents (Res@t digital): protocol for a cluster-randomized clinical trial - Paschke, Kerstin; Diestelkamp, Silke; Zapf, Antonia; Busch, Katharina; Arnaud, Nicolas; Prehn-Kristensen, Alexander; Reis, Olaf; Stark, Maria; Cloes, Jan-Ole; Schulz, Anna-Lena; Brauer, Hannah; Krömer, Thomas; et al. (Frontiers in Psychiatry, 2024)
Background: Digital media-use disorders (DMUD) in adolescents are a rising phenomenon associated with psychological distress, comorbid mental disorders, and high burden on affected families. Since the ICD-11 introduced criteria for gaming disorder, these can now be transferred to describe additional DMUD associated with social media platforms and streaming services. Most evidence for effective treatments comes from cognitive-behavioral therapy (CBT). However, interventions based on theoretical models for adolescents and their parents are widely missing leading to a significant clinical gap.: Res@t digital (Resource-Strengthening Training for Adolescents with Problematic Digital-Media Use and their Parents) is the app-based translation of the first model-based digital intervention for adolescents with DMUD and their parents based on CBT.